Slow growth and high longevity characterize the common, large Arctic brittle star, Ophiopleura borealis - Dinevik, Hanna; Altenburger, Andreas; Bluhm, Bodil A. (Frontiers in Marine Science, 2025)
The longevity (lifespan) and growth rates of a given species provide the basis for estimating its contributions to secondary production and energy flow in an ecosystem, for guiding management decisions, and determining recovery times after disturbances. For brittle stars, a class of echinoderms that dominate the megabenthos in various marine systems due to their often large populations, including those on Arctic soft bottom shelves, growth and longevity information can be estimated through growth bands in their ossicles (arm bones). Here, we estimated the maximum life span, age distribution, and growth rate of the common, large Arctic endemic brittle star, Ophiopleura borealis, from the northern Barents Sea. We counted growth bands in trawl-caught specimens using scanning electron microscope images of the innermost arm ossicles of 80 specimens spanning the known size range. These counts were corrected for overgrowth of the earliest growth bands, and growth parameters were estimated using common growth models. The age bands appeared as alternating layers of dense and less dense lines in the stereom of the ossicle fossae. The maximum corrected age band count was 39, which we infer as reflecting the age in years. This estimate is higher than for most other studied brittle stars, including polar species. Most individuals in the sampled population spanned estimated ages from 25-32 years. The growth constant k estimates of 0.09 from the Single logistic growth model and 0.01 from the specialized van Bertalanffy model indicate slow growth. The combined slow growth rate and long lifespan in Arctic brittle stars suggest that the large stocks found in Arctic regions may take a substantial time period to establish and recover from potential disturbances.